How is the Luxury Accommodation Experience Created? Case Studies from New Zealand - Harkison, Tracy (Auckland University of Technology, 2016)
A limited number of studies have been conducted on the subject of luxury accommodation experiences. These studies have tended to take a unidimensional perspective on the topic – focusing either on a management or a customer perspective – while other key actors in the provision of luxury accommodation experiences, namely service staff, have tended to be ignored. Few studies have been conducted on creating luxury accommodation experiences. Although the topic of creating experiences has been identified as an important issue in tourism experiences, it has been relatively ignored, especially in the accommodation sector, and in particular, in luxury hotels and lodges. Following an extensive review of the literature, no previous research on creating luxury hotel or lodge experiences in New Zealand has been located. The aim of this study is to examine and evaluate the creation of the luxury accommodation experience, using case studies within New Zealand. The research question addressed is: what is the luxury accommodation experience, and how is it created? This study adopted interpretivist case study methodology, utilising a multiple case study approach to the investigation and evaluation of managers’, employees’ and guests’ perspectives on creating the luxury hotel and lodge experience in New Zealand. Six luxury properties were used as case studies, and 81 participants interviewed during their ‘experience’ – the participants included 27 managers, 27 employees and 27 guests. Analysis of the data resulted in two conceptual models that identified what is the luxury lodge and hotel experience, and how it is created. The first model explains the luxury hotel and lodge experience. The model portrays the luxury hotel and lodge experience as about being in the moment; opulence; the essence of the luxury hotel or lodge; the feeling of indulgence; the location and setting of the properties; the sensations and emotions of managers, employees and guests; the physical surroundings of the properties; delivering tailored attention; hospitableness; activities that can be undertaken at the properties; and guests’ desires and expectations. Across all properties, regardless of whether they are hotels or lodges, the three strongest themes identified by research participants are being in the moment, the essence of the luxury hotel and lodge, and opulence. The second model explains how the luxury hotel and lodge experience is created. The model identifies the luxury hotel and lodge experience as created through setting the stage; the ethos of the properties; the actors’ performances; co-creation between participants; guidance; comparisons between properties; domestic and international comparisons; the brand’s values and beliefs; and projecting an image. Across all properties, regardless of whether they are lodges or hotels, the four strongest themes identified by research participants are setting the stage, the ethos of the property, the actors’ performances and co-creation between participants. The research benefits are twofold. Firstly, the research contributes to the body of knowledge in hospitality and tourism management, specifically identifying what the luxury hotel and lodge experience is and how it is created. Secondly, it provides managers with practical insights into what a luxury hotel and lodge experience is, and how they can create such an experience in their own organisations.
Keywords: Luxury hotel; Luxury lodge; Experience; Co-creation; New Zealand